Evaluation of the quality of life of adult patients admitted to the bone marrow transplantation unit - ÖZTÜRK, MEHMET SAADEDDİN; TEZCAN, SONGÜL (My University, 2023)
Introduction: The complexity of treatment and extended therapy duration associated with bone marrow transplantation directly affect the psychological well-being of the patients, create anxiety, and reduce their quality of life. The aim of our study was to evaluate the quality of life of patients admitted to the bone marrow transplantation unit. Methods: This prospective and descriptive study was conducted between January and June 2021 in an adult BMT unit in Turkey. The sociodemographic characteristics of the patients were recorded. The patient\"s quality of life was measured twice using the Functional Assessment of Cancer Therapy-Bone Marrow Transplantation (FACT-BMT) scale at the beginning of the study and 30 days later. SPSS 15 was used for the analysis. Results: A total of 40 patients were included in the study. The mean age was 46 years. Most of the patients were diagnosed with multiple myeloma and 58% had at least one comorbid disease. Most of the patients (78%) were receiving myeloablative therapy. High dose melphalan regimen was the most commonly applied regimen (25%). Thrombocytopenia was the most common side effect (14%). Although there was no change in the quality of life, it was found that the social/family well-being scores increased (p < 0.05). Conclusions: In our study, it was observed that the number of comorbid diseases was higher in patients with bone marrow transplantation. The incidence of side effects may be high in these patients. We believe that clinical pharmacists have an important role in monitoring adverse effects and improving the quality of life in bone marrow transplantation units.
Keywords: Tıp; Temel Eczacılık Bilimleri; Dahili Tıp Bilimleri; İç Hastalıkları; Onkoloji; Eczacılık; Yaşam Bilimleri; Sağlık Bilimleri; Temel Bilimler; Medicine; Basic Pharmaceutics Sciences; Internal Medicine Sciences; Internal Diseases; Oncology; Pharmacology and Therapeutics; Life Sciences; Health Sciences; Natural Sciences; Klinik Tıp (MED); Yaşam Bilimleri (LIFE); Klinik Tıp; Farmakoloji ve Toksikoloji; ONKOLOJİ; FARMAKOLOJİ VE ECZACILIK; Clinical Medicine (MED); Life Sciences (LIFE); CLINICAL MEDICINE; PHARMACOLOGY & TOXICOLOGY; ONCOLOGY; PHARMACOLOGY & PHARMACY; Farmakoloji (tıbbi); Pharmacology (medical); hematology; pharmacy service; quality of life; side effects; Transplantation